Ionopause‐like density gradients in the Martian ionosphere: A first look with MAVEN. Issue 21 (5th November 2015) - Vogt, Marissa F.; Withers, Paul; Mahaffy, Paul R.; Benna, Mehdi; Elrod, Meredith K.; Halekas, Jasper S.; Connerney, John E. P.; Espley, Jared R.; Mitchell, David L.; Mazelle, Christian; Jakosky, Bruce M.
Abstract: For unmagnetized planets, the top of the ionosphere is often marked by a sharp change in electron density and other plasma properties, called an ionopause. Here we present a statistical study of dayside ionopause‐like density gradients observed in 54% of ion density profiles from the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission spacecraft at Mars. Prior studies of the Martian ionopause have lacked simultaneous comprehensive measurements of plasma and magnetic field properties. Therefore, we use MAVEN observations of the electron density, magnetic field, and ion and electron energy spectra to study the factors that influence properties of the ionopause. On average, profiles with an ionopause are accompanied by a higher energy flux of protons at high altitudes and stronger magnetic field at low altitude than profiles without an ionopause. At altitudes above ~300 km, the O + /O2 + ratio is significantly larger for profiles with an ionopause than those without an ionopause. These findings enhance our understanding of this important plasma boundary at Mars. Key Points: We have identified an ionopause‐like density gradient in ion density profiles from MAVEN NGIMS An ionopause is most likely for orbits with high solar wind dynamic pressure, strong crustal field The ionopause is both an ion density and composition boundary, marked by a decrease of O2 +